Optimal adherence to a mediterranean diet and high muscular fitness are associated with a healthier cardiometabolic profile in collegiate students (2018)
The aim of the study was to investigate the combined association of adherence to a Mediterranean diet (MedDiet) and muscular fitness (MF) with cardiometabolic health in collegiate students. The present cross-sectional analysis consisted of 1248 (714 females) healthy collegiate students (20.1 ± 2.7 years old). Adherence to a MedDiet was assessed by a KIDMED (Mediterranean Diet Quality Index) questionnaire. Standing broad jump, standing vertical jump, and isometric handgrip dynamometry were used as indicators of MF. The cardiometabolic profile was assessed using the following components: triglycerides, blood pressure, triglycerides, high-density lipoprotein (HDL)-cholesterol, glucose, and waist circumference. Analysis of covariance shows a significant difference in the cardiometabolic profile of both genders between the high MF/low MedDiet and high MF/optimal MedDiet groups, and the low MF/low MedDiet and low MF/optimal MedDiet groups (p < 0.001). No difference was found on cardiometabolic profile between high MF/optimal MedDiet and high MF/low MedDiet, both in males and females. Additionally, logistic regression shows that both female (odds ratio (OR) = 2.01; 95% confidence interval (CI): (1.8–3.7); p = 0.02) and male (OR = 3.38; 95% CI: (1.9–5.8); p < 0.001) participants in the optimal MedDiet/high MF group had the highest odds of expressing a healthier cardiometabolic profile as compared to those in the low MF/low MedDiet group. In conclusion, a combination of high MF levels and optimal adherence to a MedDiet is associated with a healthier cardiometabolic profile; however, high MF levels seem to circumvent the deleterious effects of having a low adherence to a MedDiet. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.